An Inflammatory Profile Correlates With Decreased Frequency of Cytotoxic Cells in Coronavirus Disease 2019. (14th May 2020) - Bordoni, Veronica; Sacchi, Alessandra; Cimini, Eleonora; Notari, Stefania; Grassi, Germana; Tartaglia, Eleonora; Casetti, Rita; Giancola, Maria Letizia; Bevilacqua, Nazario; Maeurer, Markus; Zumla, Alimuddin; Locatelli, Franco; et al.
Abstract: Increased production of inflammatory cytokines and myeloid-derived suppressor cells occurs in patients with coronavirus disease 2019. These inversely correlated with perforin-expressing natural killer (NK) and CD3 + T cells. We observed a lower number of perforin-expressing NK cells in intensive care unit (ICU) patients compared with non-ICU patients, suggesting an impairment of the immune cytotoxic arm as a pathogenic mechanism.